# 24x^3-4x^2-20x=0

## Simple and best practice solution for 24x^3-4x^2-20x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 24x^3-4x^2-20x=0 equation:

Simplifying 24x^{3}+ -4x^{2}+ -20x = 0 Reorder the terms: -20x + -4x^{2}+ 24x^{3}= 0 Solving -20x + -4x^{2}+ 24x^{3}= 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '4x'. 4x(-5 + -1x + 6x^{2}) = 0 Factor a trinomial. 4x((-5 + -6x)(1 + -1x)) = 0 Ignore the factor 4.## Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0## Subproblem 2

Set the factor '(-5 + -6x)' equal to zero and attempt to solve: Simplifying -5 + -6x = 0 Solving -5 + -6x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -6x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -6x = 0 + 5 -6x = 0 + 5 Combine like terms: 0 + 5 = 5 -6x = 5 Divide each side by '-6'. x = -0.8333333333 Simplifying x = -0.8333333333## Subproblem 3

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1## Solution

x = {0, -0.8333333333, 1}

### See similar equations:

| -14h=28 | | 2x+40=3x+10 | | 8y=-16 | | w-8=44 | | 0.03x-0.1=2.6 | | -2y+2=-22 | | -10+12x=9x+3x | | 5(2x)=160 | | m-7=-15 | | 6(k+1)=2k+7 | | y^3+14y^2+49y=0 | | infT=r-tsupS | | 3x+27x=30 | | 14x-4+13x+2=180 | | n-3=14 | | 2x^2-27x+70=0 | | 180=6a | | x(35x+14)=0 | | 3x^2+27x=30 | | 2x+7y=14 | | 7x^2-6x-16=0 | | 7t=147 | | 8=10-4t | | 7x^2-15x+2=0 | | -18=18(h-4) | | 9x^2-2x+25=8x^2+8x | | 8y+4x+6y= | | 10x+7=-3 | | 12y^2+17y+6= | | p+0.12p=224 | | 3x-5=38 | | 2x^2-6x-400=0 | | (3q+1)+10=7 | | 3x+17-5x=12-(6x+3) | | 8e+3(5-e)=10 | | [3q+1]+10=7 | | 12k+5=k+49 | | 7x^2-33x-10=0 | | -3b+8=2b+48 | | -36-x=15-4x | | 21x+4=50 | | 2x+4=-27 | | -2f+14=6-2 | | -630=-30(-3b) | | 5x-10=9x+26 | | 4q-15=6q-1 | | 4t+7z=2.8 | | b+1=-3-2 | | 4x^2=28 | | X+2=-4x+7 | | -12h=132 | | 0.2(3c+15)=3(0.8c-8) | | 13-f=7 | | S=4g+4v | | 4+7z=2.8 | | 5y=y-40 | | X-35=25 | | 9b=-36 | | X^2-kx+100=0 | | Y=3x+1 | | (4-5g)(3g+2)= | | x^2=8 | | 10x+15y= | | 2x+14=5x-4 | | 5x^2-9x-2=0 |